Conservation of sequence arrangement among higher plant chloroplast DNAs: molecular cross hybridization among the Solanaceae and between Nicotiana and Spinacia. - Fluhr, R (1981)
Isolated, nick-translated Pvu II fragments of Nicotiana tabacum chloroplast DNA produce specific intra- and intergeneric hybridization signals with chloroplast DNA digests from several representatives of the Solanaceae. These data, along with similarities in restriction enzyme patterns, permit construction of physical maps for Nicotiana line 92 (a cytoplasmic substitution line), Atropa belladonna and Petunia parodii. Plastid-DNA map differences among the Solanaceae are shown to result from single base-pair substitutions as well as local deletions or insertions. Several of these differences of Nicotiana tabacum chloroplast DNA fragments to a chloroplast DNA digest of Spinacia oleracea defines a sequential arrangement of fragments for spinach DNA which is very similar to its published physical map. This is achieved although chloroplast-DNA restriction enzyme patterns from the two organisms are grossly dissimilar. Alignment differences which have been revealed involve the edges of the inverted repeat region where certain single copy stretches in tobacco have been duplicated in spinach.